IMPLEMENTASI PROGRAM EKONOMI KERAKYATAN DI DESA MALENOS BARU KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - MINATY RAFIQA; WELSON ROMPAS; JOORIE RURU (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to find out how the implementation of the People's Economy Program inMalenos Baru Village, East Amurang District, South Minahasa Regency. By using qualitative researchmethods, research studies are carried out using the theory of Edward III (in Agustino, 2008: 149-154)which says that the measurement of implementation in general can be seen from four variables, namely:Communication; Resource; Bureaucratic and Implementing Attitudes (Disposition) and BureaucraticStructure. From the results of the study, it was found that the Implementation of the People's EconomyProgram in Malenos Baru Village was classified as not good because it was seen from the four variablesstudied, namely communication, resources, bureaucratic or implementer attitudes and bureaucraticstructure which were considered not good in implementing this program and there were still variousobstacles.Keywords: Implementation, People's Economy